Management of Single Tooth Replacement in the Esthetic Region Using Immediate Implant Placement: A Case Report - Manish Rathi; Balaji Manohar (Clinical Case Reports)
ABSTRACT This case report aimed to illustrate the management of single tooth replacement in the esthetic region using immediate implant placement, highlighting the importance of interdisciplinary treatment planning and adherence to esthetic principles. A 37‐year‐old female presented with a fractured upper front tooth, necessitating immediate attention to restore esthetic.